A study on the maintenance operation of elevated highway bridges / Shah Rizal Abd Rashid - Abd Rashid, Shah Rizal (2012)
Highways design that takes into consideration maintenance aspect during the design phase affect the performance of the elevated highway bridge when it is fully operational. Most of the highways designers (architects and engineers in particular) claim they have the experience and knowledge in maintenance, but there are still many that are less cognizant of when a road designed maintenance. A survey was conducted on three concessionaires who manage maintenance around Kuala Lumpur and Selangor, where it involves a federal road and the two elevated highway bridge. The purpose of this study is to identify problems in the maintenance of elevated highways bridge today, especially those arising from the failure of design, lack of information, the use of poor quality materials, construction did not follow the specifications set because of lack of supervision and damages that often occur in an elevated highways. In sensitivity of the safety precautions at work area can cause bad things from happening, a lack of knowledge with respect to the types of temporary signs, traffic control and site locations to suit the specifications that have been listed in a guidelines to be the main factor is negligible and not complied with. As such, it is important for the management of the concession company that emphasizes the maintenance issues to minimize the problems mentioned above.